Is the word of a gentleman as good as his tweet? Policy communications of the Bank of England - Michael Lamla; Dmitri V. Vinogradov (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2021)
Policy announcements by central banks affect financial markets, but their effect on consumer beliefs is limited. This paper studies the implications of using different communication channels: established media outlets versus social media. Information on the news sources comes from our original consumer surveys administered just before and right after policy announcement events, enabling a causal inference on the announce ment effect. We focus on the Bank of England, the first central bank to actively adopt accessible language, simplifted messages and new forms of communication via its Twitter account. Based on about 10 000 individual consumer responses in 2018-2019, overall we find no statistically signiftcant effect of announcements on perceptions or expectations, yet respondents who receive news have better perceptions and expectations than those who don't. Policy announcement events trigger an increase in the share of consumers who receive monetary policy news, the share of informed consumers is higher among Twitter users, suggesting potential benefits from Twitter communication with the public. However, Twitter users tend to overestimate inflation and interest rates, make a greater expectations/perception error. In addition they report higher confidence in their estimates. In terms of expectations quality, spreading the word of the Central bank via conventional mass media appears to be more effective than tweets.
Keywords: E52; E58; 330; perceptions; expectations; central bank communication; consumer; Twitter